Musik sebagai Sarana Untuk Mengekspresikan Diri: Analisis Lirik Lagu “Membasuh” Karya Hindia - Arfian Suryasuciramdhan; Maulana Yusuf; Nessya Mayla Faiza; Rendi (Universitas Maritim AMNI Semarang, 2024)
In this modern era, the continuous progression of music has had a critical effect on the rise of different sorts of songs. Music has become an integral part of society, serving as a loyal companion in various moments of life. The connection between humans and music has become undeniable. Music is not just a tool for entertainment, but also a powerful means of communication, allowing individuals to express themselves. From expressing feelings to conveying ideas and opinions, music serves as a vessel capable of depicting various aspects of human life. In this context, this research aims to analyze how the lyrics of the song